Literature review on the effect of physical and mental health on financial well-being - Isaac D. Swensen; Carly Urban (Institute of Labor Economics (IZA), 2023)
Adverse health conditions have the potential to financially cripple American households. This report reviews the large literature that considers the ways in which health-both physical and mental-impacts household finances. The review largely includes studies with U.S. populations and spans many disciplines: economics, public health, law, medicine, psychology, public policy, and sociology. The overwhelming finding is that deteriorating health, new health conditions, and even health shocks-such as injuries-negatively impact the financial health of households. First, unanticipated out-of-pocket health costs reduce or deplete the household savings, sometimes forcing household members to forego necessary consumption. This reduced consumption could directly harm their health, providing a direct feedback loop into the relationship between health and finances. Second, declining health or new health conditions often force people out of the labor market for an extended period. This reduces household earnings and either forces other household members to work more to compensate for the earnings loss or further harms the household balance sheet. The effects of mental health conditions are often more detrimental than the onset of severe physical health conditions. The detrimental effects of health conditions on household finances are generally largest for those with the fewest protections in place: those with fewer assets, those without insurance coverage, and those with less education. However, the labor market consequences are sometimes largest for the highest earners. Existing policies can blunt the effects of health on finances. Comprehensive health insurance, specifically for the chronically ill, those with high-cost conditions, and those covered under Medicaid, generates the greatest benefits for overall financial health. Paid sick leave and subsidized caregiving limit the effects of work interruptions when someone in the household falls ill. Promising existing policies that do not require federal changes include pausing loan obligations, financial literacy, and pairing healthcare choice with cost information.
Keywords: I18; I10; I31; I38; 330; health shock; financial well-being; household finances